ANALISIS PERTANGGUNG JAWABAN HUKUM BAGI PELAKU PENEBANGAN LIAR YANG MENGAKIBATKAN BENCANA ALAM DI KECAMATAN ANGGERAJA KABUPATEN ENREKANG - Muhammad Risal Amram; Asram A.T. Jadda; Asrul Hidayat; Hartono Hamzah (At-Tanwir Law Review, 2025)
This study aims to determine the legal responsibility for illegal logging perpetrators that result in natural disasters, and to determine the challenges faced in enforcing the law against illegal logging perpetrators in Anggeraja District, Enrekang Regency. The research method used is a normative-empirical approach, namely combining a study of applicable laws and regulations with field findings. Data collection techniques are carried out through literature studies, observations, interviews, and documentation with sources from the Environmental Service, Forestry Service, village officials, NGOs, and the Anggeraja District community. The results of the study show that law enforcement against illegal logging perpetrators still faces many obstacles, both in terms of the weakness of law enforcement officers, the involvement of individuals in illegal networks, and low public awareness. Illegal logging has been proven to be the main cause of natural disasters such as floods and landslides in the area. Although there are regulations that regulate it such as Law No. 18 of 2013 and Law No. 32 of 2009, their implementation has not been optimal. Therefore, strategic steps are needed in the form of increased supervision, firm legal action, and ongoing public education.